Diatom and dinoflagellate cysts determination from Young Sound fjord, North-East Greenland - Meri Marianne Mäkelä; Tiia Luostarinen; Sofia Ribeiro; Kaarina Weckström; Mikael K Sejr; Mie Hylstofte Sichlau Winding; Maija Heikkilä (PANGAEA, 2025)
Datasets collected from Young Sound fjord, Northeast Greenland, between 2013 and 2018 including sediment trap and surface sediment samples that were analysed for diatoms and dinoflagellate cysts. For sediment trap samples, an automated PPS4/3 sediment trap with an aperture of 0.05 m2 was installed near the fjord entrance (74.322°N; 20.269°W) at 60-m water depth, 15 m above the seafloor as part of the Greenland Ecosystem Monitoring (GEM) programme. The rotation for the trap was set to 7 to 91 -day intervals. The surface sediment samples were collected in 2013 and 2015 as individual trips from small rubber boats using a Rumohr lot corer, multi corer or Kayak corer. Sediment trap samples were analysed for relative abundances and fluxes of dinoflagellate cysts and diatoms. Surface sediment samples were analysed for relative abundances of diatoms and dinoflagellate cysts. For identification a Zeiss Axio Imager.A2 upright research microscope was used with a Plan-Apochromat 100 exttimes/1.4 oil immersion objective, phase contrast optics and a total magnification of exttimes1000 for diatoms and a 60x oil immersion objective and a total magnification of exttimes600 for dinoflagellates.